THE RELATIONSHIP BETWEEN SOCIO-ECONOMIC BACKGROUND AND RENTAL HOUSING CRITERIA AMONG UNIVERSITY STUDENTS - Nur Atifah Jamalludin; Nur Amira Syazwina Shafie; Siti Izzati Hamzah; Nursyahirah Rosli; Hanis Hanani Mad Isa; Afida Ahmad; Norin Rahayu Shamsuddin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examines the impact of socio-economic disparities on university students' rental housing preferences in Malaysia, a country where the rising cost of living and limited on-campus housing options pose significant challenges, especially for students from lower-income backgrounds (B40). The study aims to explore how socio-economic status influences students' housing decisions and the subsequent effects on their academic performance and well-being. Using a cross-sectional research design, data was collected from 103 students at a public university in Malaysia’s northern region through an online survey. The data was analyzed using one-way ANOVA, Kruskal-Wallis, and chi-square tests to identify differences in housing preferences across socio-economic groups. The findings reveal that students from lower-income families prioritize affordability, often compromising on housing quality and proximity to campus, while those from higher-income backgrounds (M40 and T20) can afford better-quality housing closer to the university. These disparities in housing choices underscore the need for targeted interventions by university administrators and policymakers to ensure that all students, regardless of their socio-economic status, have access to safe, affordable, and adequate housing. Addressing these issues is crucial for supporting the academic success and overall well-being of students from diverse socio-economic backgrounds. , , ,